Immunomodulatory Function of HBeAg Related to Short-Sighted Evolution, Transmissibility, and Clinical Manifestation of Hepatitis B Virus - Kramvis, Anna; Kostaki, Evangelia-Georgia; Hatzakis, Angelos; Paraskevis, Dimitrios (Frontiers in Microbiology, 2018)
Hepatitis B virus (HBV) infection, a global public health problem can be asymptomatic, acute or chronic and can lead to serious consequences of infection, including cirrhosis and hepatocellular carcinoma. HBV, a partially double stranded DNA virus, belongs to the family Hepadnaviridae, and replicates via reverse transcription of an RNA intermediate. This reverse transcription is catalyzed by a virus-encoded polymerase that lacks proof reading ability, which leads to sequence heterogeneity. HBV is classified into nine genotypes and at least 35 subgenotypes, which may be characterized by distinct geographical distributions. This HBV diversification and distinct geographical distribution has been proposed to be the result of the co-expansion of HBV with modern humans, after their out-of-Africa migration. HBeAg is a non-particulate protein of HBV that has immunomodulatory properties as a tolerogen that allows the virus to establish HBV infection in vivo. During the natural course of infection, there is seroconversion from a HBeAg-positive phase to a HBeAg-negative, anti-HBe-positive phase. During this seroconversion, there is loss of tolerance to infection and immune escape-HBeAg-negative mutants can be selected in response to the host immune response. The different genotypes and, in some cases, subgenotypes develop different mutations that can affect HBeAg expression at the transcriptional, translational and post-translational levels. The ability to develop mutations, affecting HBeAg expression, can influence the length of the HBeAg-positive phase, which is important in determining both the mode of transmission and the clinical course of HBV infection. Thus the different genotypes/subgenotypes have evolved in such a way that they exhibit different modes of transmission and clinical manifestation of infection. Loss of HBeAg may be a sign of short-sighted evolution because there is loss of tolerogenic ability of HBeAg and HBeAg-negative virions are less transmissible. Depending on their ability to lead to HBeAg seroconversion, the genotype/subgenotypes exhibit varying degrees of short-sighted evolution. The “arms race” between HBV and the immune response to HBeAg is multifaceted and its elucidation intricate, with transmissibility and persistence being important for the survival of the virus. We attempt to shed some light on this complex interplay between host and virus.